Caring and Collaborating Across Cultures? Migrant Care Workers' Relationships with Care Recipients, Colleagues and Employers - TIMONEN, VIRPI; DOYLE, MARTHA (My University, 2010)
The literature on migrant care workers has tended to place little emphasis on themultiple relationships thatmigrant carers formwith care recipients, employers/managers and work colleagues. This article makes a contribution to this emerging field, drawing on data from qualitative interviews carried out with 40 migrant care workers employed in the institutional and domiciliary care sectors in Dublin, Ireland. While the analysis revealed generally positive carer?care recipient relationships, significant racial and cultural tensions were evident within the vertical and especially the horizontal relationships in the care workplace. The article argues that these findings highlight the need for additional research on the relationships formed in the long-term care sector and further theorizing on the meaning and importance of the affective components of care work within increasingly commodified care markets.
PUBLISHED
Keywords: migrant; care; work; racism; gender; integration; migrant; care; work; racism; gender; integration